2020
DOI: 10.1111/cid.12930
|View full text |Cite
|
Sign up to set email alerts
|

Immediately loaded mini‐implants supporting mandibular overdentures: A one‐year comparative prospective cohort study

Abstract: BackgroundLittle is known about differences between mini‐implants and conventional immediately loaded implants for overdentures.ObjectivesTo compare clinical outcomes using two immediately loaded conventional or mini‐implants for mandibular overdentures.Materials and MethodsEdentulous patients receiving either conventional (4.1 mm) or mini‐implants (2.9 mm or less), based on available bone width were analyzed. All implants were immediately loaded with mandibular overdentures installed using locator attachments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(35 citation statements)
references
References 17 publications
1
34
0
Order By: Relevance
“…The distribution of bone density and quantity of both groups were comparable, as previously reported by the present authors. 15 Depending on group allocation, two conventional diameter or two mini implants were installed between the mental foramina, ideally in the canine sites (considering satisfactory bone dimensions available), or with a minimum distance between the implants of 10 mm using minimal flap reflection, following previous described methodology. 16 Guide holes were drilled in the mandibular complete denture to direct the surgeon during implant placement providing an image guided technique.…”
Section: Surgical Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of bone density and quantity of both groups were comparable, as previously reported by the present authors. 15 Depending on group allocation, two conventional diameter or two mini implants were installed between the mental foramina, ideally in the canine sites (considering satisfactory bone dimensions available), or with a minimum distance between the implants of 10 mm using minimal flap reflection, following previous described methodology. 16 Guide holes were drilled in the mandibular complete denture to direct the surgeon during implant placement providing an image guided technique.…”
Section: Surgical Interventionmentioning
confidence: 99%
“…Inc.) abutments were first hand tightened and the operative site was then secured with monofilament sutures, following a previously described surgical protocol. 15 Patients were instructed not to remove the lower overdenture until the time of suture removal (7 days later) and to maintain a soft diet. Seven days after surgery, the overdenture was removed from the mouth.…”
Section: What This Study Addsmentioning
confidence: 99%
“…The surgical and prosthodontic protocols used herein have been described in a previous study. 16 In summary, depending on which group the patient was assigned to, two conventional diameter or two mini-implants were installed between the mental foramina using a mid-crestal incision with vertical releasing incisions to expose the ridge. After confirming that the minimum desired peak insertion torque required for immediate loading was reached, the Locator (Zest Patients were instructed not to remove the lower overdenture until the time of suture removal and to maintain a soft diet.…”
Section: Surgical Intervention and Prosthodontic Protocolmentioning
confidence: 99%
“…14,15 In this context, a previous study using Locators abutments found significantly better clinical and biological results for two conventional diameter implants, as compared with two mini-implants. 16 On the other hand, little is known on OHrQoL and satisfaction differences in patients using overdentures supported by Locator abutments on two conventional or two mini-implants. Therefore, the aim of this study was to compare the OHrQoL and satisfaction with overdentures in a clinical cohort study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation